Biopsychosocial predictors of coping strategies of patients postmyocardial infarction. Issue 5 (4th August 2016) - Son, Heesook; Friedmann, Erika; Thomas, Sue A; Son, Youn‐Jung
Abstract : Data from the Patients and Families Psychological Response to the Home Automated External Defibrillator Trial were used to examine the relationship between biopsychosocial variables and patients' coping strategies postmyocardial infarction. This study is the secondary data analysis of longitudinal observational study. A total of 460 patient–spouse pairs were recruited in January 2003 to October 2005. Hierarchical linear regression analysis examined biological/demographic, psychological and social variables regarding patients' coping scores using the Family Crisis Oriented Personal Evaluation Scale. Lower social support and social support satisfaction predicted lower total coping scores. Being younger, male gender and time since the myocardial infarction predicted lower positive coping strategy use. Higher anxiety and lower social support were related to fewer positive coping methods. Lower educational levels were related to increased use of negative coping strategies. Reduced social support predicted lower total coping scores and positive coping strategy use and greater passive coping style use. Social support from a broad network assisted with better coping; those living alone may need additional support. Social support and coping strategies should be taken into consideration for patients who have experienced a cardiac event. Summary Statement: What is already known about this topic? The experience of a first‐time acute myocardial infarction is a traumatic event and might influence well‐being for a significant time period. Coping strategies are a very delicate issue for people who have experienced myocardial infarction. What this paper adds Social support was the only significant predictor of coping strategy use in postmyocardial infarction patients after controlling for other biopsychosocial factors. Social support might be related to sex and time since last myocardial infarction. The implications of this paper for policy/?practice/research/education Nurses should be aware that patients' coping strategies need to be taken into account when planning intervention before hospital discharge. Nursing intervention strategies to improve coping strategy use after myocardial infarction should focus on the holistic interaction between biological–psychological–social domains rather than addressing them as separate aspects of the individual or environment.